Incidence of Skin and Respiratory Immune-Related Adverse Events Correlates With Specific Tumor Types in Patients Treated With Checkpoint Inhibitors - Rose, Lynn M.; DeBerg, Hannah A.; Vishnu, Prakash; Frankel, Jason K.; Manjunath, Adarsh B.; Flores, John Paul E.; Aboulafia, David M. (Frontiers in Oncology, 2021)
Checkpoint inhibitors (CPIs) increase antitumor activity by unblocking regulators of the immune response. This action can provoke a wide range of immunologic and inflammatory side effects, some of which can be fatal. Recent studies suggest that CPI-induced immune-related adverse events (irAEs) are robust biomarkers linked to improved survival. However little is known about the mechanisms driving most irAEs. This study was undertaken to evaluate the influence of tumor diagnosis and preexisting clinical factors on the types of irAEs experienced by cancer patients treated with CPIs. The correlation between irAEs and overall survival (OS) was also assessed. All cancer patients treated with atezolizumab (ATEZO), ipilimumab (IPI), nivolumab (NIVO), or pembrolizumab (PEMBRO) at Virginia Mason Medical Center between 2011 and 2019 were evaluated. IrAEs were graded according to the Common Terminology Criteria for Adverse Events (Version 5) and verified independently. Statistical analyses were performed to assess associations between irAEs, pre-treatment factors, and OS. Of the 288 patients evaluated, 59% developed irAEs of any grade, and 19% developed irAEs of grade 3 or 4. A time-dependent survival analysis demonstrated a clear association between the occurrence of irAEs and OS (P < 0.001). A 6-week landmark analysis adjusted for body mass index confirmed an association between irAEs and OS in non-Small Cell Lung Cancer (NSCLC) (P < 0.03). An association between melanoma and skin irAEs (P < 0.01) and between NSCLC and respiratory irAEs (P = 0.03) was observed, independent of CPI administered. Patients with preexisting autoimmune disease experienced a higher incidence of severe irAEs (P = 0.01), but not a higher incidence of irAEs (P = 0.6). A significant association between irAEs and OS was observed in this diverse patient population. No correlation was observed between preexisting comorbid conditions and the type of irAE observed. However, a correlation between skin-related irAEs and melanoma and between respiratory irAEs and NSCLC was observed, suggesting that many irAEs are driven by a specific response to the primary tumor. In patients with NSCLC, the respiratory irAEs were associated with a survival benefit.